Some Factors in State TANF Participation by Immigrants: An Examination Using the Group Threat Hypothesis. - Cheng, Tyrone C.; Lo, Celia C. (Journal of Poverty)
This study asked what happens as the proportion of immigrants on states' Temporary Assistance for Needy Families (TANF) rolls changes, employing the group threat hypothesis to analyze data dating 2000–2017. The data examined were extracted from compilations of information by federal agencies indicating states' population by race/ethnicity, poverty and unemployment rates, and TANF participation by immigrants (as a percentage of total participation). Results showed states with relatively larger African American populations often had a lower percentage of immigrants enrolled in their TANF programs. Results also showed a negative association between percentage of TANF participation by immigrants and state unemployment rate. Policy implications are discussed.